Mucoadhesive and muco-penetrating delivery systems for eradication of Helicobacter pylori - Arora, Saahil; Bisen, Gaurav; Budhiraja, RD (Asian Journal of Pharmaceutics (AJP), 2014)
Helicobacter pylori (H. pylori), the major culprit for peptic ulcer, has a unique way of survival in harsh acidic environment of the stomach by colonizing deep in the gastric mucosal layer. Failure of conventional therapies against H. pylori for complete eradication has major limitations like low residence time of delivery system in stomach, poor penetration of drug in gastric mucosa, acidic degradation of antibiotics, and development of antibiotics resistance. The poor penetration of antibiotics through thick viscoelastic mucosal gel results in incomplete eradication of H. pylori. Various investigators have formulated novel gastro-retentive drug delivery systems such as floating systems, mucoadhesive systems, pH-sensitive gel systems, and muco-penetrating delivery systems for increasing the concentration of antibiotic in close proximity to the site of H. pylori infection. This review summarizes the novel drug delivery approaches investigated during the last few years and suggests that a high eradication rate can be achieved by therapy comprising of muco-penetrating delivery systems of antibiotics against H. pylori.